An investigation into metaphor use in learner language: the interaction of word class and L1 - Yaser Hadidi; Nastaran Behshad (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
This study aims at investigating the use of metaphor in learner language with a focus on interaction of word class and L1. The findings of previous studies on metaphor use in learner language point to the fact that metaphor is found in all word classes in learners’ written production, but that some word classes clearly favor metaphorical usage more than others. In similar fashion, the present investigation looked into the interaction between metaphor, word class, and L1, although within a single register and text type, i.e. argumentative essays produced by 20 novice writers. The model underlying the current study was Conceptual Metaphor Theory by Lakoff and Johnson (1980). Identification of metaphors was carried out based on MIP (Metaphor Identification Procedure) (Pragglejaz Group, 2007), a reliable and explicit tool for marking and identifying metaphorically used words. The hypothesis, based on previous research establishing this finding, was that prepositions top the list in this regard, being by far the most metaphorical word class. The cognitive predispositions made available by the student’s L1 are also of importance in this equation. Similar research would advance our understanding of the role of metaphor teaching, and in what form and to what degree it should be explicitly carried out.